Exploring the perspective of health and well-being among orang asli: Case study of Jakun - Bin Alwi M.N.R.; Ibrahim M.I.B.M.; Baharuddin S.S.B.; Bin Salahuddin S.N. (Science and Engineering Research Support Society, 2023)
This study is focus on health perspectives and its impact on the Orang Asli well-being. Through aboriginal worldview, health can be studied from physical, mental, emotional and spiritual components. Using qualitative study, we aim to understand Orang Asli perspectives of health and its components and the way it impacts their overall well-being. Participants were purposively selected from the largest tribe of Orang Asli in Malaysia. Based on the analysis, all components of health in the predetermined construct are important for them and affect their well-being. Further discussions are made on each construct and components particularly in relation to well-being. 2019 SERSC.